STRATEGI PENYAJIAN BERITA PADA PORTAL BATAMPOS.CO.ID - Kasirul Fadli; Indrawan; Said Nuwrun Thasimmin; Haryati; Mitrayati (PROGRAM STUDI ILMU KOMUNIKASI, 2022)
In this study, the authors used a qualitative-descriptive approach, with data sources namely primary data (research informants) and secondary data (reference books). Collecting data through observation, interviews, documentation, and literature review. The technique of determining the informant was carried out purposively, namely based on the capacity that provided convenience and willingness in the interview. The data was then analyzed using data analysis techniques carried out inductively (from data to theory). Based on research conducted on several informants, the results show that the strategies that have been carried out on the Batampos.Co.Id portal are: The strategy is supported by three things, 1) the strategy in selecting issues is made effective in choosing a different angle so that it is not the same as the print. or mostly online media, 2) the issue placement strategy consists of two things, namely important and interesting issues, 3) a news development strategy by combining the concepts of conventional news presentation and follow-up news. Based on the results of research on news presentation strategies and editorial strategies in maintaining news accuracy related to the speed and presentation of news on the batampos.co.id portal, it can be concluded that: Determining the selection of issues in the news, Placement of news issues, which means always looking at the positive side and The negative is by holding editorial meetings every day, because not all issues that are crowded in the community have a positive affect and batampos.co.id doesn't want to bring up news just because of ratings, presentation and news development, namely presenting quality news based on the ideals of mass media principles.